Morphological characterisation of five brazilian species of Fidicinoides (Hemiptera: Cicadidae) - SANTOS, RODRIGO S.; MARTINELLI, NILZA M. (Revista Colombiana de Entomología, 2011)
The objective of this study was to describe and illustrate the morphological characteristics of some species of Brazilian Fidicinoides to aid in their identification. Descriptions and illustrations are given of the head, thorax, abdomen, right forewing and the last urosternite of the male of the Fidicinoides besti, Fidicinoides brunnea, Fidicinoides duckensis, Fidicinoides pseudethelae and Fidicinoides sucinalae species. The main diagnostic characteristics of these species are markings on pronotum and/or mesonotum and male sternite VIII characteristics.